2015
DOI: 10.1074/jbc.m114.611459
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Temperature-dependent Activation of Transient Receptor Potential Vanilloid 1 (TRPV1) by Phospholipids in Planar Lipid Bilayers

Abstract: Background: Regulation of the temperature-dependent activity of TRPV1 channels with phosphoinositides is not well understood. Results: Phosphoinositides directly facilitate heat activation of TRPV1 reconstituted in neutral planar lipid bilayers. Different anionic lipids evoke TRPV1 channel activity with distinct open probability and conductance states. Conclusion: Phospholipids are required for heat-induced activation of TRPV1. Significance: Phosphoinositides are essential regulators of TRPV1 gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
3
38
1
Order By: Relevance
“…5D) [65]. In a subsequent paper it was shown that PG could also support heat-induced TRPV1 activity in planar lipid bilayers in a lipid mixture of PG:PC:PE = 3:3:1 with high open probability, but lower unitary conductance [114]. …”
Section: Dependence Of Trpv1 Activity On Phosphoinositides and Itsmentioning
confidence: 99%
See 2 more Smart Citations
“…5D) [65]. In a subsequent paper it was shown that PG could also support heat-induced TRPV1 activity in planar lipid bilayers in a lipid mixture of PG:PC:PE = 3:3:1 with high open probability, but lower unitary conductance [114]. …”
Section: Dependence Of Trpv1 Activity On Phosphoinositides and Itsmentioning
confidence: 99%
“…Since then, several reviews on more general topics discussed phosphoinositide regulation of TRPV1 [29, 40, 78, 95, 96]. Due to the unceasing interest and recent developments in this controversial topic [8, 65, 66, 84, 105, 114], however, I felt that a comprehensive and specific discussion is warranted on phosphoinositide regulation of TRPV1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70,71 Different approaches used for manipulating the cellular PIP 2 level may underlie the difference, with some including PIP 2 into the whole-cell recording pipette, 65,67 and some applying PIP 2 directly to an inside-out excised patch, 63,68,69 whereas others reconstituting PIP 2 and purified TRPV1 in an artificial liposome or into planar lipid bilayers. 61,64 It should be noted that most of these studies are conducted in expression or reconstitution system, which may also contribute to variable conclusions. A missing study is to determine the role of PIP 2 in native sensory neurons.…”
Section: Modulation Of Trpv1mentioning
confidence: 99%
“…However, there is a continuing controversy regarding the exact role of PIP 2 in TRPV1 activation, with some supporting an inhibiting role, 60,61 and some advocating an stimulating effect, [62][63][64][65][66][67][68][69] whereas others favoring both activating and inhibiting roles depending on certain conditions. 70,71 Different approaches used for manipulating the cellular PIP 2 level may underlie the difference, with some including PIP 2 into the whole-cell recording pipette, 65,67 and some applying PIP 2 directly to an inside-out excised patch, 63,68,69 whereas others reconstituting PIP 2 and purified TRPV1 in an artificial liposome or into planar lipid bilayers.…”
Section: Modulation Of Trpv1mentioning
confidence: 99%